Description of Extension Activities in Transmigrant Communities in Banyuasin and Ogan Ilir District South Sumatra Province, Indonesia - Malta (GoAcademica Research & Publishing, 2020)
Extension activities play an important role in developing human resources for transmigrants in farming. Extension aims to develop targets to become human resources capable of improving the quality of life independently.The purpose of this study was to describe the extension activities to transmigrant communities in Banyuasin and Ogan Ilir Regencies, South Sumatra. The study was conducted from May 2016 to January 2017. The total population was 3,537 transmigrant households. The number of the samples in this study was determined using Slovin formula. The study involved 359 respondents determined by stratified random sampling. The research data consisted of primary data and secondary data. The primary data was obtained through structured interviews, in-depth interviews, and field observations. The results of the study showed that the conditions for extension activities in the two districts were low for all measured aspects, namely: intensity of extension, suitability of materials, suitability of methods, and capacity of extension personnel.